Characterization of the circRNA–miRNA–mRNA Network to Reveal the Potential Functional ceRNAs Associated With Dynamic Changes in the Meat Quality of the Longissimus Thoracis Muscle in Tibetan Sheep at Different Growth Stages - Bao, Gaoliang; Zhao, Fangfang; Wang, Jiqing; Liu, Xiu; Hu, Jiang; Shi, Bingang; Wen, Yuliang; Zhao, Li; Luo, Yuzhu; Li, Shaobin (Frontiers in Veterinary Science, 2022)
Circular RNAs (circRNAs) have been shown to have a regulatory role in animal skeletal muscle development. However, their function in LT muscle growth and development of Tibetan sheep remain undefined. In this study, RNA sequencing was performed to reveal the temporal regularity of circRNA expression and the effect of circRNA-miRNA-mRNA ceRNA regulatory network on meat quality of LT muscle in Tibetan sheep at different growth stages (4-month-old, 4 m; 1.5-years-old, 1.5 y; 3.5-years-old, 3.5 y; 6-years-old, 6 y). The results indicated that there were differences in carcass performance and meat quality of Tibetan sheep at different ages. especially, the meat tenderness significant decreased (P<0.05) along with age increasing. Further analysis had found that a total of 193, 168, 148 and 202 differentially expressed (DE) circRNAs were identified from contiguous period transcriptome comparative groups of 4 m vs 1.5 y, 1.5 y vs 3.5 y, 3.5 y vs 6 y and 4 m vs 6 y, respectively. GO functional enrichment indicated that the source genes of DE circRNAs were mainly involved in the function of the protein binding, myofibril and organelle assembly. And Calcium signaling pathway, signaling pathways regulating pluripotency of stem cells and AMPK signaling pathway, etc. were significant enriched in the KEGG enrichment. The circRNA-miRNA-mRNA ceRNA interaction network analysis showed that circRNAs such as novel_circ_000786, novel_circ_007750 and novel_circ_01067 combined with miR-29-3p and miR-185-5p regulate the expression of LEP, SCD, FASN related to the transformation of muscle fiber types in the AMPK signaling pathway. The oxidized muscle fibers transformed into the glycolytic muscle fibers with age increasing, and the content of intramuscular fat (IMF) was lower and the diameter of the muscle fiber was larger in the glycolytic muscle fibers, which ultimately made the meat tenderness decreased. The study revealed the role of circRNA in the transformation of skeletal muscle fiber types in Tibetan sheep and its influence on meat quality. It improves our understanding of the role of circRNA in Tibetan sheep muscle development.